Decision Making in Health Education and Health Promotion Interventions Using the Evidential Reasoning Approach - Mehdi Ebrahimnia; Ali Akhoundi; Mahboubeh Rouhollahi; Alireza Taghdisi (Iranian Association of Health Education and Health Promotion, 2017)
Decision making in health education and health promotion is often faced with problems that are affected by different factors simultaneously. In this case, researchers have to deal with multi-criteria decision-making problems. Considering the fact that many factors have an effect on the decisions that are to be made in health education and health promotion, using a method that can deal with both qualitative and quantitative criteria and data with a degree of uncertainty is highly beneficial. The evidential reasoning approach is a multi-criteria decision-making method that can be used to select the most preferable option, based on comments from different experts. The benefits of this method are the ability to receive and use data in different formats with or without uncertainty. Thereby resulting in more reliable and sophisticated answer than many other multi-criteria decision-making methods.  Paper type: Review Article.